2020
DOI: 10.1371/journal.ppat.1008528
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparisons of Toxoplasma gondii and its near relative Hammondia hammondi reveal dramatic differences in the host response and effectors with species-specific functions

Abstract: Toxoplasma gondii and Hammondia hammondi are closely-related coccidian intracellular parasites that differ in their ability to cause disease in animal and (likely) humans. The role of the host response in these phenotypic differences is not known and to address this we performed a transcriptomic analysis of a monocyte cell line (THP-1) infected with these two parasite species. The pathways altered by infection were shared between species~95% the time, but the magnitude of the host response to H. hammondi was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
(208 reference statements)
0
8
0
Order By: Relevance
“…Another explanation could be that the persistent installation of T. gondii in its host involves a dynamic regulation of combined cellular and molecular immunoregulatory networks [52][53][54][55], which can impact the newly infecting Plasmodium parasite using similar pathways. This could result in less production of anti-PfAMA1 IgG to effectively fight plasmodial parasites.…”
Section: Plos Onementioning
confidence: 99%
“…Another explanation could be that the persistent installation of T. gondii in its host involves a dynamic regulation of combined cellular and molecular immunoregulatory networks [52][53][54][55], which can impact the newly infecting Plasmodium parasite using similar pathways. This could result in less production of anti-PfAMA1 IgG to effectively fight plasmodial parasites.…”
Section: Plos Onementioning
confidence: 99%
“…However, they may have a role in establishing the infection. Activation of both pathways is aimed at inhibiting apoptosis and progression through the S phase and into G2 / M. This could indicate the importance of the cell cycle stage of the host cell during infection [294]. Notably, the toxoplasma genome codes for endogenous miRNAs, so it is possible that parasites use these to modify the host's cellular functions [279], similarly to that observed for mammalian viruses [276,295].…”
Section: Mirna In Host-toxoplasma Gondii Interactionmentioning
confidence: 98%
“…Additionally, Myc activates many genes associated with cell growth, including E2F genes, such as E2F1, required for the initial entry to the cell cycle from a quiescent state [293]. E2F1 expression is also increased in cells infected by T. gondii [294]. Paradoxically, the mir-17-92 cluster negatively modulates the E2F1 expression [291].…”
Section: Micrornas In the Host–parasite Interactionmentioning
confidence: 99%
“…These GRAs are ultimately found in various compartments [reviewed in Clough and Frickel (2017) and Mercier and Cesbron‐Delauw (2015)], including: (a) within the PV lumen, some being involved in the generation of an elaborate, nanotubular network; (b) within and on the PVM, including its host‐cytosolic face, and in one case leading to the association of host mitochondria (see below); and 3) within the host cytosol and nucleus after being exported out of the PV. In addition to being secreted by intracellular parasites into the PV lumen, GRAs can be secreted by extracellular parasites, enabling the parasites to impact the extracellular milieu, thereby potentially impacting uninfected cells and general tissue functions (Leroux et al., 2015; Wong et al., 2020). Finally, and although the data for this is incomplete, there is some evidence that the dense granules may not be homogeneous with respect to their protein cargo, possibly allowing the parasite a finer level of control in the packaging and timing of export of GRA effectors (Mercier & Cesbron‐Delauw, 2015).…”
Section: Gra Effectors Provide a Second Wave That Can Associate With mentioning
confidence: 99%
“…Cells infected with Toxoplasma exhibit significant cell cycle alteration, and while the specifics of the alteration vary by cell type, it has generally been reported that Toxoplasma tachyzoites advance the cell into S phase (Molestina et al., 2008) and arrest it in the G2 phase, prior to mitosis (Brunet et al., 2008; Wong et al., 2020). Under certain circumstances this results in a binucleated phenotype as the infected cells fail to undergo proper cytokinesis during mitosis (Velasquez et al., 2019).…”
Section: Gra16 and Hce1/teegr Impact Pathways Associated With The Hosmentioning
confidence: 99%